Peluang dan Tantangan Implementasi Kurikulum Merdeka Belajar: Sebuah Studi Interview di Sekolah Penggerak dan Mandiri Berubah - Ragil Nazar, Erhy; Nasir, Nasir; Bagea, Ishak; Abubakar (Kelola: Jurnal Manajemen Pendidikan, 2024)
The implementation of the Merdeka Belajar curriculum in State Elementary Schools (SES) in Kendari city marks a progressive step in adapting education to contemporary needs. This study aims to understand the implementation of this curriculum in SES Kendari city and identify the challenges and opportunities associated with its implementation. The research employs a qualitative approach through interviews with seven informants, including teachers and school principals from SES involved in the evolving independent school program. Interview data are analyzed through transcription, coding, and reflective analysis. The findings indicate that despite facing challenges such as teacher readiness and resource availability, the Merdeka Belajar curriculum has a positive impact on increasing student engagement and teacher creativity. Support from the Department of Education also emerges as a key factor in the successful implementation. Therefore, this research provides a deep understanding of the implementation of the Merdeka Belajar curriculum in SES Kendari city and highlights the importance of enhancing support and implementation strategies to achieve more inclusive and responsive educational goals.